2009
DOI: 10.1007/s11242-009-9399-9
|View full text |Cite
|
Sign up to set email alerts
|

Slow Motion of an Assemblage of Porous Spherical Shells Relative to a Fluid

Abstract: The body-force-driven motion of a homogeneous distribution of spherically symmetric porous shells in an incompressible Newtonian fluid and the fluid flow through a bed of these shell particles are investigated analytically. The effect of the hydrodynamic interaction among the porous shell particles is taken into account by employing a cell-model representation. In the limit of small Reynolds number, the Stokes and Brinkman equations are solved for the flow field around a single particle in a unit cell, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…The net force acting on the sedimenting porous shell vanishes at the steady state. Applying this constraint to the summation of eqs , , and , we obtain the sedimentation velocity of the spherical porous shell as expressed by eq 11 with where U 0 is the sedimentation velocity of an uncharged porous shell. , Because both the fixed charges of the porous shell and the local induced sedimentation potential gradient are of the order Q , the effect of the fixed charge density on the shell velocity resulting from their interaction starts from the second order Q 2 .…”
Section: Sedimentation Velocitymentioning
confidence: 99%
See 2 more Smart Citations
“…The net force acting on the sedimenting porous shell vanishes at the steady state. Applying this constraint to the summation of eqs , , and , we obtain the sedimentation velocity of the spherical porous shell as expressed by eq 11 with where U 0 is the sedimentation velocity of an uncharged porous shell. , Because both the fixed charges of the porous shell and the local induced sedimentation potential gradient are of the order Q , the effect of the fixed charge density on the shell velocity resulting from their interaction starts from the second order Q 2 .…”
Section: Sedimentation Velocitymentioning
confidence: 99%
“…where U 0 is the sedimentation velocity of an uncharged porous shell. 21,22 Because both the fixed charges of the porous shell and the local induced sedimentation potential gradient are of the order Q, the effect of the fixed charge density on the shell velocity resulting from their interaction starts from the second order Q 2 . It can be found that U 2 depends on the inner-to-outer radius ratio a/b, electrokinetic radius κb (ratio of the outer radius to the Debye length), and shielding parameter λb (ratio of the outer radius to the flow penetration length) of the shell as well as the ionic diffusion coefficients in the electrolyte solution.…”
Section: Sedimentation Velocitymentioning
confidence: 99%
See 1 more Smart Citation